As necessidades em saúde de indivíduos adultos Porto Rico - PR - Merino, Maria de Fátima Garcia Lopes (2007)
This qualitative study fits into the social perspective for approaching health matters, and was developed from community data of adult inhabitants in the city of Porto Rico, Paraná State, Brazil. The objective of this research was to understand their conceptions of health and sickness, prevention habits and the therapeutic itinerary adopted by adult residents of that city. As theoretical references, we adopted Leininger's Theory of Transcultural Care Diversity and Universality, as we understood that care can only take place if cultural aspects are valued, and the Therapeutic Itinerary, in light of the concepts of Medical Needs, which presented a justification for the variations observed among medical consumption by different social classes, as defined by Luc Botanski. It is a descriptive-exploratory study of a qualitative nature, developed among 29 adults, male and female, between 20 and 59 years of age, residing within the city limits of Porto Rico. Data was collected between July 3 and 27, 2006, and took place at the homes of the interviewees, using semi-structured interviews and non systematized observation. For data analysis, we adopted the Thematic Analysis method proposed by Minayo (1998). Results revealed that, for more than half of the subjects (51.7%), to be healthy meant having no signs of illness. Other factors mentioned regarding what characteristics were most important to consider an individual healthy were: to be happy, to work, to have adequate sleep and rest, to have motivation for daily activities, to be young and have good physical appearance, not to have food restrictions, and to have illness control and prevention habits. The most worrisome illnesses mentioned were cancer (70%) and AIDS (38%). It was observed that, although men are more exposed to the risk factors analyzed (tobacco and alcohol) than women (53% and 25%, respectively), only women demonstrated any concern and desire to quit these habits, revealing a greater concern with health-related matters. Similar conduct was observed in relation to health behavior as women recognize and give importance to signs and symptoms of illness as they develop, seeking earlier for solutions through the official healthcare, most men wait for the illness to manifest itself before seeking help. Likewise, most women (75%) make regular use of preventive methods of healthcare, while the same is not true for men (only 16% of individuals older than 50 have undergone the preventive prostate exam). The greatest health concern among women is also manifested through the perception of an instance of illness in the previous 12 months, three times greater among women (75%) than among men (23%). As for the Therapeutic Itinerary adopted, self-medication was the most widely adopted resource (41.4%), with little difference among the genders. However, the same does take place in regard to the second most used resource, which is the official healthcare service, as the percentages of women who use it as their first option is practically double that of men (43% and 23%, respectively). Lastly, going to the drugstore was mentioned as the first action when faced by the onset of illness by 24.1% of interviewed subjects, but the percentage of men who follow this practice is three times greater than that of women who do the same (38.5% and 12.5%, respectively). It was further observed that a considerable share of individuals (35%) was dissatisfied with the services offered by the official healthcare system in the city, such as the service hours, the reduced availability for consultations in relation to demand, the difficulty in scheduling consultations and/or exams, the non-existence of medical specialties, difficulty in obtaining medication, low credibility of medical services offered, and rapport issues with health professionals. These findings demonstrate the difficulties in caring, especially for the men's health, by the city's official healthcare system, and the need for greater action by health staff, as well as guiding and adapting these services to the needs of their users.